Social construction of technology (SCoT) from generation X’s shopping experiences to omnichannel as new way of shopping - Irvan Permana; Karina Gan (Universitas Bunda Mulia, 2022)
Omnichannel is considered a new way of shopping that integrates online and offline methods to offer seamless shopping experiences. Omnichannel requires consumers adaptation to use the internet, mobile devices, and social media as tools for seamless shopping experiences. Based on 2021 YouGov’s report on omnichannel retail, 83% of Indonesians already used dual channels to shop, including generation X. How does generation X accept omnichannel and its technology as a new way of shopping? Using Social Construction of Technology (SCoT) theory, generation X is positioned as a relevant social group, and their interpretative flexibility on how they give meaning to omnichannel as a new way of shopping will be analyzed; followed by understanding their closure or common agreement towards webrooming, showrooming, buying online pick-up in store, and buying online return in-store as the attributes of omnichannel; then finally analyzing their stabilization in accepting omnichannel as a new way of shopping. Using the interpretative phenomenological analysis, this research was conducted by interviewing generation X to understand their acceptance of omnichannel. The results of this research show that generation X has no hesitation to omnichannel, but they saw it as additional services rather than integration of seamless shopping experiences.